Microlearning berbasis digital dalam pendidikan: Tinjauan literatur dan implikasinya terhadap pembelajaran di Indonesia - Nuriyah, Afrizatun (Maliki Interdisciplinary Journal, 2026)
Digital-based microlearning is a learning approach that emphasizes the delivery of content in small, focused, and easily accessible units through digital technology. This approach is considered relevant to the characteristics of 21st-century learners who face time constraints, short attention spans, and high dependence on digital devices. This article aims to systematically review the concept of digital-based microlearning through a literature review and analyze its implications for educational practices in Indonesia. The research method employed is a literature review of relevant scholarly articles, conference proceedings, and research reports related to microlearning and digital learning. The findings indicate that microlearning has the potential to enhance learning effectiveness, learner motivation, and flexibility in the learning process. In the context of Indonesian education, microlearning can serve as a strategic alternative to support online and blended learning. However, its implementation requires adequate infrastructure, teacher competence, and well-designed content tailored to learners’ characteristics.